Visual study of ex-pin phenomena for SFR with metal fuel under initial phase of severe accidents by using simulants. Issue 9 (1st September 2016) - Heo, Hyo; Park, Seong Dae; Jerng, Dong Wook; Bang, In Cheol
ABSTRACT: In the present Korean sodium-cooled fast reactor (SFR) program, early dispersion of the molten metal fuel within a subchannel is suggested as an inherent safety strategy in the initiating phase of a hypothetical core disruptive accident (HCDA). This safety strategy provides a negative reactivity driven by the melt dispersion; therefore, it could reduce the possibility of occurrence of a severe recriticality event. In the initiating phase, the melt could be injected into the subchannel horizontally by the internal pressure of the fuel pin. Complex phenomena occur during intermixing of the melt with the coolant after the horizontal injection of the melt. It is rather difficult to understand the several combined mechanisms that occur that are related to the dispersion and fragmentation of the melt. Thus, it seems worthwhile to study the horizontal injection of melt at lower temperatures, which could help to observe the dispersion phenomenon and understand the fragmentation mechanism. In this work, for a parametric study, tests were performed under structural conditions, coolant void conditions, and boiling conditions. As a result, in some cases, the injected molten materials were stuck around the injection hole. On the other hand, the molten materials were dispersed upward sufficiently well under the boiling condition when R123 was used as the coolant. The built-up vapor pressure was found to be one of the driving forces for the upward dispersion of the molten materials.